Analisis Tata Kelola Kelembagaan Ekonomi Desa (Studi Pada Usaha Mikro di Desa Banjarsari) - Putri, Kinanti Prianggara; Septia, Resti; Algunadi, Muhammad; Maulana, Piki (Prodi S1 Administrasi Bisnis Universitas Sangga Buana YPKP, 2025)
This study aims to examine the management of village economic institutions in supporting the development of micro-enterprises in Banjarsari Village. Village economic institutions play a crucial role in creating an ecosystem that supports the growth of micro-enterprises through various aspects, such as policies, access to capital, mentoring, and strengthening market networks. The research method used is a case study with a qualitative approach, which includes interviews, observations, and document analysis of micro-enterprise actors and relevant village officials. The findings reveal that the management of institutions in Banjarsari Village faces several challenges, such as a lack of coordination between related institutions, limited access to information for micro-enterprise actors, and a lack of ongoing training programs. Nevertheless, there is great potential to strengthen village institutions through optimizing the role of the Village-Owned Enterprise (BUMDes), enhancing human resource capacity, and collaborating with external parties. This study recommends improvements in institutional management to be more inclusive and transparent, aiming to increase the role of micro-enterprises in the village economy and ensure long-term sustainability and community welfare.